Social work practice and outcomes in rehabilitation: a scoping review - Freymüller, Nadja; Knoop, Tobias; Meyer-Feil, Thorsten (Frontiers in Rehabilitation Sciences, 2024)
Social work is a long-established profession in health care and rehabilitation. Reviewing the evidence on effects of social work interventions shows inconsistencies, with several studies indicating positive, negative, or no significant effect at all. Against this background, the purpose of this paper is to provide an international overview of the research on social work practice in rehabilitation. Two research questions about the activities performed by social workers in rehabilitation settings and the reported outcomes to evaluate social work interventions were guiding the analysis. A scoping review was conducted in order to identify these activities and reported outcomes. The literature search was carried out in two databases (PubMed, SocINDEX). Additionally, the authors searched manually for literature in rehabilitation science and social work journals. Inclusion criteria encompassed the involvement of social workers and a description of their activities. The context in which social work's practice had to take place was a rehabilitation setting. A total of 2,681 records could be identified by searching the databases, journals, proceedings and reference lists. 66 sources met the predefined inclusion criteria. A majority of the identified activities that social workers perform are case related. Topics that may occur in these case encounters are the social environment of the patient, financial/social security, work-related issues and others. Of particular note are activities such as assessment, counseling and education. When applying the ICF framework, the outcomes are distributed across almost all components with an emphasis on Participation. This review demonstrates that social work has a vital role in the interprofessional rehabilitation team on an international level. However, there is still a need for more research about the effectiveness of social work interventions. We identified internationally common social work core activities/issues and derived a proposal for specific outcomes for future evaluation research.